INOVASI MEDIA FLIPBOOK ‘MEFOSIS’ UNTUK MENINGKATKAN PEMAHAMAN DAN KEMAMPUAN BERPIKIR KOGNITIF SISWA TENTANG METAMORFOSIS DI SDN 2 PADOKAN KASIHAN BANTUL - Nadia Wahyu Umi Kholifah; Arip Febrianto (STKIP Subang, 2025)
The investigation into the creation of educational media Grade IV primary school students can benefit from MEFOSIS (Metamorphosis Flipbook Media) by developing their cognitive thinking skills. Research and Development (R&D) of the 4D model (Define, Design, Develop, Disseminate) is the methodology employed. With the use of field tests and limited tests, experts in theory and learning tools verify the accuracy of the tool to enhance learning. With a score of 87.50% from material experts and 95.00% from media experts, the validation results demonstrate that MEFOSIS is very practicable to use.The results of students (96% in limited tests and 97% in field tests) and teachers (86%) indicate that the medium is very practical. The average value of the pretest to posttest increased from 56 to 76 (restricted test) and from 60 to 83 (field test), demonstrating the media's effectiveness. The findings of the paired sample t-test were significant (p = 0.000 <0.05), suggesting that pupils' cognitive abilities had significantly increased. In conclusion, MEFOSIS has been shown to be workable, useful, and efficient when used in fundamental science teaching and learning activities.